PEMIKIRAN ISLAM TENTANG HUBUNGAN NEGARA DENGAN AGAMA - Nasaruddin, Nasaruddin (Hunafa: Jurnal Studia Islamika, 2009)
A study of relationship between state and religion includes three paradigms: integralistic, symbiotic, and secularistic, which are products of legal reasoning to Quranic messages in the context of human history. In the case of Indonesia, it embraces Pancasila, which is neither based on religious nor secular systems. However, muslim communities in Indonesia become political targets due to the factors which include the weakness of Islamic politics that is uprooted from Islamic fundamental values in terms of political aspirations, and the application of western democracy that is not compatible with the traditions and cultures of Indonesia.Kata Kunci: pemikiran Islam, Negara, agama